Unreported RSK2 missense mutation in two male sibs with an unusually mild form of Coffin-Lowry syndrome. Issue 10 (1st October 1999) - Manouvrier-Hanu, S; Amiel, J; Jacquot, S; Merienne, K; Moerman, A; Coëslier, A; Labarriere, F; Vallée, L; Croquette, M F; Hanauer, A
Abstract : An unreported missense mutation of the ribosomal S6 kinase 2 ( RSK2 ) gene has been identified in two male sibs with a mild form of Coffin-Lowry syndrome (CLS) inherited from their healthy mother. They exhibit transient severe hypotonia, macrocephaly, delay in closure of the fontanelles, normal gait, and mild mental retardation, associated in the first sib with transient autistic behaviour. Some dysmorphic features of CLS (in particular forearm fullness and tapering fingers) and many atypical findings (some of which were reminiscent of FG syndrome) were observed as well. The moderate phenotypic expression of this mutation extends the CLS phenotype to include less severe mental retardation and minor, hitherto unreported signs. The missense mutation identified may be less deleterious than those previously described. As this mutation occurs in a protein domain with no predicted function, it could be responsible for a conformational change affecting the protein catalytic function, since a non-polar amino acid is replaced by a charged residue.